Answer:
68%
Step-by-step explanation:
According to the empirical rule:
68% of the data values lie within one standard deviation from the mean i.e. from z = -1 to z = 1 we have 68% of the data values95% of the data values lie within two standard deviations of the mean99.7% of the data values lie within three standard deviations of the meanSo first we have to find how many standard deviations away from the mean are the given two values. This can be done by converting them into z scores.
The formula to calculate the z-score is:
[tex]z=\frac{\text{Data Value}-\text{Mean}}{\text{Standard Deviation}}[/tex]
Using the given values in above formula, we get:
For x = 2.3
[tex]z = \frac{2.3-2.9}{0.6}=-1[/tex]
For x = 3.5
[tex]z = \frac{3.5-2.9}{0.6}=1[/tex]
This means we have to tell how many data values are within one standard deviation of the mean. According to the empirical rule 68% of the values are between z= -1 and z = 1. So the answer is 68%
68% of students at the college have a GPA between 2.3 and 3.5.
What is the empirical rule?The empirical rule states that for a normal distribution, 68% of the values falls within one standard deviation, 95% of the values falls within two standard deviation, and 99.7% of the values falls within three standard deviation.
Hence:
For a mean of 2.9 and a standard deviation of 0.6.
68% falls within 2.9 ± 0.6 = (2.3, 3.5)
68% of students at the college have a GPA between 2.3 and 3.5.
Find out more on empirical rule at: https://brainly.com/question/10093236
What are the solutions of the equation 4x2 + 3x = 24 – x? –3, 2, or 4 –3 or 2 –2, 3, or 4 –2 or 3
Answer:
x = -3 or x = 2Step-by-step explanation:
[tex]4x^2+3x=24-x\qquad\text{subtract 24 from both sides}\\\\4x^2+3x-24=-x\qquad\text{add}\ x\ \text{to both sides}\\\\4x^2+4x-24=0\qquad\text{divide both sides by 4}\\\\x^2+x-6=0\\\\x^2+3x-2x-6=0\\\\x(x+3)-2(x+3)=0\\\\(x+3)(x-2)=0\iff x+3=0\ \vee\ x-2=0\\\\x+3=0\qquad\text{subtract 3 from both sides}\\x=-3\\\\x-2=0\qquad\text{add 2 to both sides}\\x=2[/tex]
The given equation, 4·x² + 3·x = 24 - x, can be simplified and factorized
to give the solution as; -3, 2
Which methods are use to find the solution of the equation?The solution to the given equation, 4·x² + 3·x = 24 - x, is the point of
intersection of the parabola, 4·x² + 3·x, and the line, 24 - x
The solution is therefore, found as follows;
4·x² + 3·x = 24 - x
4·x² + 3·x - (24 - x) = 0
4·x² + 4·x - 24 = 0
Dividing by 4, gives;
4·(x² + x - 6) = 0
x² + x - 6 = 0 ÷ 4 = 0
x² + x - 6 = 0Factorizing, the above quadratic equation, we have;
(x + 3) × (x - 2) = 0
x = -3, or x = 2The solution of the equation is therefore;
-3, 2Learn more about factorizing quadratic equations here:
https://brainly.com/question/83151
f(x)=8x^2-2x+3
g(x)=12x^2+4x-3
What is h(x)=f(x)-g(x)?
A) h(x)=20x^2+2x
B) h(x)=-4x^2-6x
C) h(x)=-4x^2-6x+6
D) h(x)=-4x^2+2x
Answer:
-4x^2-6x+6
Step-by-step explanation:
We are asked to subtract g from f.
So the problem is:
[8x^2-2x+3]-[12x^2+4x-3]
So I'm going to distribute and write without [].
8x^2-2x+3-12x^2-4x+3
Now I'm going to pair up any like terms:
8x^2-12x^2-2x-4x+3+3
Simplifying:
-4x^2-6x+6
Answer: The correct option is
(C) [tex]h(x)=-4x^2-6x+6.[/tex]
Step-by-step explanation: We are given the following two functions :
[tex]f(x)=8x^2-2x+3,~~~~~g(x)=12x^2+4x-3.[/tex]
We are to find the value of h(x) if h(x) = f(x) - g(x).
To find the value of h(x), we must subtract the expression of g(x) from the expression of f(x).
The value of h(x) can be calculated as follows :
[tex]h(x)\\\\=f(x)-g(x)\\\\=(8x^2-2x+3)-(12x^2+4x-3)\\\\=8x^2-2x+3-12x^2-4x+3\\\\=-4x^2-6x+6.[/tex]
Thus, the required value of h(x) is [tex]-4x^2-6x+6.[/tex]
Option (C) is CORRECT.
The cost, y, of red apples can be represented by the equation y = 2x, where x
is the number of pounds of red apples.
The graph shows the cost of green apples.
Which type of apple costs more per pound?
Answer:
red apples
Step-by-step explanation:
cause for 1 pound, a red apple will cost 2 dollars, while for 1 pound, a green apple will cost less
Answer:
Red apples
Step-by-step explanation:
Since the cost of red apples is given by the equation y = 2x
where x = is number of pounds of red apples
Therefore clearly it can seen from the equation that the slope of this equation will be more steeper than the slope of the cost of the cost the green apples.
Now since the slope is more steep, therefore we can conclude that the red apples will cost more than the green apples for per pound of apples.
Thus, red apples will cost more per pound than green apples.
If you bought a stock for $45 dollars and could sell it fifteen years later for three times what you originally paid. What was your return on owning this stock?
Answer:
90$
Step-by-step explanation:
45$
45*3=135
But your return was 3 times the price, so subtract a 45.
135-45=90$
Answer: $90
Step-by-step explanation:
Given : The cost of one stock = $45
And the value of that stock after 15 years is 3 times the paid price.
i.e. The value of that stock after 15 years = [tex]3\times45=\$135[/tex]
Then, the return on owning this stock = [tex]\text{Value after 15 years -Paid price}[/tex]
[tex]=\$135-\$45=\$90[/tex]
Therefore, the return on owning this stock = $90
What is the following simplified product? Assume x>/= 0
Answer: second option.
Step-by-step explanation:
We know that:
[tex]\sqrt[n]{a^n}=a[/tex]
[tex](a^m)(a^n)=a^{(m+n)[/tex]
Then we can simplify the radicals:
[tex]2\sqrt{8x^3}(3\sqrt{10x^4}-x\sqrt{5x^2})=(2\sqrt{2^2*2*x^2*x})(3\sqrt{10x^4}-x\sqrt{5x^2})=\\\\=2*2*x\sqrt{2x}=3x^2\sqrt{10}-x*x\sqrt{5}\\\\=4x\sqrt{2x}(3x^2\sqrt{10}-x^2\sqrt{5})[/tex]
Since:
[tex](a\sqrt[n]{x})*(b\sqrt[n]{y})=ab\sqrt[n]{xy}[/tex]
We can apply Distributive property:
[tex]4x\sqrt{2x}(3x^2\sqrt{10}-x^2\sqrt{5})\\\\12x^3\sqrt{20x}-4x^3\sqrt{10x}[/tex]
Simplifying:
[tex]12x^3*2\sqrt{5x}-4x^3\sqrt{10x}\\\\24x^3\sqrt{5x}-4x^3\sqrt{10x}[/tex]
Answer:
B
Step-by-step explanation:
edg2021
Which choice below is a boxplot for the following distribution?
58, 50, 48, 46, 44, 42, 40, 38, 36, 34, 32, 30, 28, 26, 24, 22, 14
A. Boxplot A
B. Boxplot B
C. Boxplot C
D. Boxplot D
E. Boxplot E
Answer:
Boxplot A
Step-by-step explanation:
Answer: Option 'A' is correct.
Step-by-step explanation:
Since we have given that
58, 50, 48, 46, 44, 42, 40, 38, 36, 34, 32, 30, 28, 26, 24, 22, 14.
We will write in ascending order:
14 ,22 ,24 ,26 ,28,30 ,32 ,34, 36 ,38, 40, 42 ,44 ,46 ,48,50,58.
Since there are 17 terms in the above data.
So, Median would be 36.
As box plot shows the middle point of the data i.e. median.
In box plot A it shows the correct median at the middle i.e. 50% of the scores.
Hence, option 'A' is correct.
A. y-2=2(x-3)
B. y-3=2(x-2)
C. y-10=2(x-1)
D. y-1=2(x-10)
Answer:
C. y-10=2(x-1)
Step-by-step explanation:
We have two points on the line, we can find the slope
m = (y2-y1)/(x2-x1)
= (10-2)/(1--3)
= 8/(1+3)
=8/4
=2
The slope is 2
We can use point slope form using the point (1,10)
y-y1 = m(x-x1)
y-10 = 2(x-1)
Answer:
C. y - 10 = 2(x - 1)Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
(x₁, y₁) - point
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
We have the points (-3, 2) and (1, 10). Substitute:
[tex]m=\dfrac{10-2}{1-(-3)}=\dfrac{8}{4}=2[/tex]
Using the point (-3, 2):
[tex]y-2=2(x-(-3))\\\\y-2=2(x+3)[/tex]
Using the point (1, 10):
[tex]y-10=2(x-1)[/tex]
How do u do this please help!!
Answer:
C. 3 gal. 3 qt. 1 pt.Step-by-step explanation:
1 gallon = 4 quarts
5 gallons 2 quarts 1 pint = 4 gallons 6 quarts 1 pint
(5 gallons 2 quarts 1 pint) - (1 gallon 3 quarts)
= (4 gallons 6 quarts 1 pint) - (1 gallon 3 quarts)
= 3 gallons 3 quarts 1 pint
f(x) = x^2 - 5
g(x) = 4x - 4
Find (f-g) (5)
4
-5
-4
5
Answer:
The correct answer option is: 4.
Step-by-step explanation:
We are given the following two functions and we are to find the value of [tex] ( f - g ) ( 5 ) [/tex]:
[tex]f(x) = x^2 - 5[/tex]
[tex]g(x) = 4x - 4[/tex]
Finding [tex] ( f - g ) ( x ) [/tex]:
[tex] ( f - g ) ( x ) [/tex] [tex]= (x^2-5)-(4x-4) = x^2-4x-5+4[/tex]
[tex]( f - g ) ( x ) = x^2-4x-1[/tex]
So, [tex]( f - g ) ( 5 ) = (5)^2-4(5)-1 = 4[/tex]
Answer:
4
Step-by-step explanation:
f(x) = x^2 - 5
g(x) = 4x - 4
(f-g) (x)= x^2 - 5 - (4x - 4)
Distribute the minus sign
= x^2 - 5 - 4x + 4
= x^2 -4x-1
Let x = 5
(f-g) (5) = 5^2 -4(5) -1
=25 - 20 -1
=5-1
=4
The appropriate translation of the phrase 11 more than 20 percent of a number is:
0.2n+11
True or false?
Answer: True
Step-by-step explanation: 20% can also be written as 0.2 and if you know the number then you would multiply it by 0.2, then if you needed to add 11 that is exactly how you would write that equation
How to convert 3.5 gallons into quarts. There are 4 quarts in 1 gallon.
Answer:
look at the picture attached
If f(x) = 4 – x2 and g(x) = 6x, which expression is equivalent to (g – f)(3)?
Answer:
6(3) - (4 - 3²) = 6(3) - 4 + 3²Step-by-step explanation:
[tex]f(x)=4-x^2,\ g(x)=6x\\\\(g-f)(x)=g(x)-f(x)\\\\(g-f)(x)=6x-(4-x^2)\\\\(g-f)(3)-\text{put x = 3 to the equation}\\\\(g-f)(3)=6(3)-(4-3^2)[/tex]
which number has the lesser value 5.13 or5.099
Answer: 5.099
Step-by-step explanation:
technically, 5.099 is 5.10
10 is bigger than 13 so
5.13 > 5.10
The blue segment below is a radius of O. What is the length of the diameter of the circle?
Answer:
B, 14.6 units.
Step-by-step explanation:
The answer is be because:
the diameter = radius times 2
radius= 7.3
diameter=7.3*2
=14.6
Therefore the answer is, B
Answer: B. 14.6 units
Step-by-step explanation: The diameter of a circle is two times the length of the radius. So multiply the radius by 2.
7.3 x 2 = 14.6
The diameter of the circle is 14.6 units.
What is the slope of the line containing (6, -7) and (5, -9)?
A) 1
B) -2.
C) 2
D) 16
Answer: C
Step-by-step explanation:
y2-y1/x2-x1
-9+7/5-6 = 2
/5×+4/ =/×+9/ solve for x
Answer:
[tex]\large\boxed{x=\dfrac{5}{4}\ \vee\ x=-\dfrac{13}{6}}[/tex]
Step-by-step explanation:
[tex]|5x+4|=|x+9|\iff5x+4=x+9\ or\ 5x+4=-(x+9)\\\\5x+4=x+9\qquad\text{subtract 4 from both sides}\\5x=x+5\qquad\text{subtract x from both sides}\\4x=5\qquad\text{divide both sides by 4}\\x=\dfrac{5}{4}\\\\5x+4=-(x+9)\\5x+4=-x-9\qquad\text{subtract 4 from both sides}\\5x=-x-13\qquad\text{add x to both sides}\\6x=-13\qquad\text{divide both sides by 6}\\x=-\dfrac{13}{6}[/tex]
Evaluate -x+4x when x=-2
Use the substitution method
-x+4x when x=-2
-(-2)+4(-2) Positive number * ( multiplying)Negative number=Negative number
2-8
=-6
Answer is -6
which statement must be true about the diagram?
Answer:
It's the third choice.
Step-by-step explanation:
M < NKM and m < MKL both equal 61 degrees
so KM is a bisector of < NKL.
Answer:
C:ray MK is an angle bisector of angle NKL
Step-by-step explanation:
We have to find the true statement about the diagram
[tex]\angle JKN=58^{\circ}[/tex]
[tex]\angle NKM=61^{\circ}[/tex]
[tex]\angle MKL=61^{\circ}[/tex]
[tex]\angle NKM=\angle MKL=61^{\circ}[/tex]
When a ray is a bisector of any angle then the angles are equal which are made by bisection of the angle.
By using this definition
The ray MK is a bisector of angle NKL because angle NKM and MKL are equal.
Answer:C
If sinx= sqrt(3)/2, and 90° < x < 180°, what is cos(x/2)?
Answer:
cos 60° = 1/2
Step-by-step explanation:
* Lets explain how to solve the question
- If angle Ф lies in the first quadrant then sin Ф , cos Ф and tan Ф
are positive values
- The equivalent angle of angle Ф in the second quadrant is 180° - Ф
and sin Ф is positive but cos Ф and tan Ф are negative
- The equivalent angle of angle Ф in the third quadrant is 180° + Ф
and tan Ф is positive but cos Ф and sin Ф are negative
- The equivalent angle of angle Ф in the fourth quadrant is 360° - Ф
and cos Ф is positive but sin Ф and tan Ф are negative
* Lets solve the problem
∵ sin x = √3/2
∵ 90° < x < 180°
∴ ∠ x lies in the second quadrant
∴ m∠ x = 180° - Ф
- Let sin Ф = √3/2
∴ Ф = sin^-1 (√3/2)
∴ Ф = 60°
∵ x = 180° - Ф
∴ x = 180° - 60°
∴ x = 120°
- To find cos(x/2) divide 120° by 2
∵ cos (120°/2) = cos (60°)
∴ cos 60° = 1/2
How would I solve for y?
Answer:
y=40
Step-by-step explanation:
Step 1: Add 1 to both sides.
3y−1+1=119+1
3y=120
Step 2: Divide both sides by 3.
3y /3 = 120 /3
y=40
Which is the graph of the equation y-1=2/3(x-3)?
The graph of the given equation is the line that passes through (0,-1) and (3/2,0) and whose slope is m = 2/3 and this can be determined by using the slope-intercept form of the line.
Given :
Equation - [tex](y -1) = \dfrac{2}{3}(x-3)[/tex]
The following steps can be used to draw the graph of the given equation:
Step 1 - Write the given equation.
[tex](y -1) = \dfrac{2}{3}(x-3)[/tex]
Step 2 - Simplify the above equation.
[tex]y = \dfrac{2}{3}x - 2 + 1[/tex]
[tex]y = \dfrac{2}{3}x - 1[/tex]
Step 3 - Draw the graph of (y = x).
Step 4 - Find the y-intercept and the slope of the above equation.
c = -1
[tex]m = \dfrac{2}{3}[/tex]
Step 5 - So, the graph of the given equation is the line that passes through (0,-1) and (3/2,0) and whose slope is m = 2/3.
For more information, refer to the link given below:
https://brainly.com/question/10712002
The graph of the equation is a line that passes through the origin (0, 0) and has a slope of 2/3.
Explanation:The given equation is y - 1 = ⅓(x - 3). To graph this equation, we can start by rearranging it in slope-intercept form, y = mx + b, where m is the slope and b is the y-intercept.
First, let's isolate y by adding 1 to both sides of the equation:
y = ⅓(x - 3) + 1
Now, simplify the expression on the right side:
y = ⅓x - 1 + 1
y = ⅓x
So, the equation y - 1 = ⅓(x - 3) represents a line with a slope of ⅓ and a y-intercept of 0. To graph this line, we can plot the y-intercept at (0, 0) and use the slope to draw the line.
The graph of this equation is a line that passes through the origin (0, 0) and has a slope of ⅓. Any point on this line can be represented as (x, ⅓x).
Learn more about Graphing equations here:https://brainly.com/question/30842552
#SPJ3
What is the slope of the line given by the equation below?
y = 4x-2
Answer:
slope: 4
Step-by-step explanation:
y = 4x-2 is in the form y = mx +b where m is the slope and b is the y intercept
4 is the slope and -2 is the y intercept
Answer:
4Step-by-step explanation:
The slope-intercept form of an equation of a line:
[tex]y=mx+b[/tex]
m - slope
b - y-intercept
We have [tex]y=4x-2[/tex].
Therefore
the slope [tex]m=4[/tex]
the y-intercept [tex]b=-2[/tex]
Solve the given inequality. If necessary, round to four decimal places.
134a < 19
Question 4 options:
a < 0.287
a < 4.2641
a < 1.3863
a < 2.5649
Answer:
[tex]a < 0.287[/tex]
Step-by-step explanation:
we have
[tex]13^{4a} < 19[/tex]
Solve for a
Apply log both sides
[tex]log(13^{4a}) < log(19)[/tex]
Remember the rule
㏒(a^n) = n ㏒(a)
so
[tex](4a)log(13) < log(19)[/tex]
Divide by 4 log(13) both sides
[tex]a < log(19)/[4log(13)][/tex]
[tex]a < 0.2870[/tex]
if a + b + C = -1 and x + y + z = -8, what is -8z -8x + 5a + 5c - 8y + 5b
Answer:
59
Step-by-step explanation:
a + b + C = -1
x + y + z = -8
We want 5a so multiply the first equation by 5
5(a + b + c) = -1*5
5a+5b+5c = -5
We want -8x so multiply the second equation by -8
-8(x + y + z) = -8*-8
-8x-8y-8x = 64
Add these equations together
5a+5b+5c = -5
-8x-8y-8x = 64
---------------------------
-8x -8y-8x+5a+5b+5c = 59
Rearrange the order
-8z -8x + 5a + 5c - 8y + 5b = 59
Answer:
59
Step-by-step explanation:
The first step here is to rewrite -8z -8x + 5a + 5c - 8y + 5b as
-8x - 8y - 8z + 5a + 5b + 5c.
This is the same as -8(x + y + z) + 5(a + b + c).
Subbing -8 for (x + y + z) and -1 for (a + b + c), we get -8(-8) - 5, or 59.
what is a reasonable estimate for the problem? 3 3/4 x -2/5
Answer:
You can not break that down any further if x does not equal anything and the equation is not equal to anything.
Step-by-step explanation:
Write quadratic equation whose roots are 1 and -3 and whose leading coefficient is 4
Answer:
4x^2 + 8x - 12 = 0.
Step-by-step explanation:
We first write it in factor form.
4(x - 1)(x + 3) = 0
4(x^2 + 2x - 3) = 0
4x^2 + 8x - 12 = 0 (answer).
Answer:
4x^2 + 8x - 12 = 0
Step-by-step explanation:
A quadratic equation with roots a and b has the equation (x - a)(x - b) = 0.
You roots are 1 and -3.
The equation is
(x - 1)(x - (3)) = 0
(x - 1)(x + 3) = 0
We can multiply it out.
x^2 + 3x - x - 3 = 0
x^2 + 2x - 3 = 0
Since we need the leading coefficient to be 4, we multiply both sides by 4.
4x^2 + 8x - 12 = 0
Try this trick out on a friend. Tell your friend to place a dime in one hand and a penny in the other hand. Explain that you can determine which hand is holding the penny.
Here’s how to do it:
a. Ask the friend to multiply the value of the coin in his or her RIGHT hand by 4, 6, or 8 and then to multiply the value of the coin in his or her LEFT hand by 3, 5, or 7.
b. Now ask the friend to add the two results together and tell you the total.
c. If the total is EVEN, the penny is in the RIGHT hand. If the total is ODD, the penny is in the left hand.
The math trick described allows you to figure out which hand a friend is holding a penny in by having them multiply the value of the coins in their hands by specific numbers, adding the results, and determining whether the total is even or odd.
Explanation:The subject at hand pertains to a mathematical trick used to determine in which writing a friend is holding a penny. To execute the scheme, follow the procedure:
Ask your friend to multiply the coin's value in their right hand by 4, 6, or 8. Then, instruct them to bear the coin's weight in their left hand by 3, 5, or 7.Next, ask them to add the two results and the total.the penny is in the friend's right hand if the total is even. If the sum is odd, the penny is in their left hand. Here's why: When a dime (10 cents) is multiplied by any integer, the result will be an even number. But a penny (1 cent) multiplied by any number will keep its parity (odd or even). So, if the total sum is weird, the left-hand number, odd, must have been contributed by the penny.Learn more about math tricks here:
https://brainly.com/question/2273245
#SPJ3
In triangle ABC, m∠ABC = (4x – 12)° and
m∠ACB = (2x + 26)°. Yin says that if x = 19, the triangle must be equilateral. Is he correct? Justify your answer.
Answer:
A triangle is equilateral if all three angles are same. but here two angles are 64° but third angle is 52°. so, Yin is incorrect.
Step-by-step explanation:
x = 19,
Putting value of x to find m∠ABC and m∠ACB
m∠ABC = (4x – 12)°
m∠ABC = (4(19) – 12)°
m∠ABC = (76 – 12)°
m∠ABC = 64°
m∠ACB = (2(19) + 26)°
m∠ACB = (38 + 26)°
m∠ACB = 64°
now we know sum of angles of triangle is 180°. We can find the measure of third angle.
180 = 64+64 +x
x= 180 - 64 - 64
x = 52°
A triangle is equilateral if all three angles are same. but here two angles are 64° but third angle is 52°. so, Yin is incorrect.
Sample Response: No, Yin is not correct. If
x = 19, the measure of angle ABC = 4(19) – 12 = 64. Therefore, the two base angles measure 64°. An equilateral triangle is equiangular, so each angle would have to measure 60° because there are 180° in a triangle.
What did you include in your response? Check all that apply.
Yin is not correct.
The measure of the congruent base angles is 64°.
The measures of the angles in an equilateral triangle are 60°.
What’s 18/20 simplified
Find the GCD (or HCF) of numerator and denominator
GCD of 18 and 20 is 2
Divide both the numerator and denominator by the GCD
18 ÷ 2
-----------
20 ÷ 2
Reduced fraction:
9
----
10
[tex]\huge\text{Hey there!}[/tex]
[tex]\huge\text{What's }\huge\dfrac{18}{20}\huge\text{ simplified?}[/tex]
[tex]\huge\text{Both terms have the GCF}[/tex] [tex]\huge\text{(Greatest Common Factor) of 2}[/tex]
[tex]\huge\text{So, divide both numbers by 2.}[/tex]
[tex]\huge\dfrac{18\div2}{20\div2}[/tex]
[tex]\huge\text{18}\huge\div\huge\text{2 = 9}[/tex]
[tex]\huge\text{9 is the numerator (top \#)}[/tex]
[tex]\huge\text{20}\huge\div\huge\text{2 = 10}[/tex] [tex]\huge\text{10 is the denominator (bottom \#)}[/tex]
[tex]\boxed{\boxed{\huge\text{Answer: }\huge\dfrac{9}{10}}}\huge\checkmark[/tex]
[tex]\text{Good luck on your assignment \& enjoy your day!}[/tex]
~[tex]\frak{LoveYourselfFirst:)}[/tex]
I need to simplify for the question
Answer:
[tex]\tt x^2+3xy+4y^2[/tex]
Step-by-step explanation:
[tex]\tt(x-2y)^2+7xy\\\\=x^2-4xy+4y^2+7xy\\\\=x^2+3xy+4y^2[/tex]
Answer:
[tex] x^2 + 3xy + 4y^2 [/tex]
Step-by-step explanation:
[tex] (x - 2y)^2 + 7xy = [/tex]
[tex] = (x - 2y)(x - 2y) + 7xy [/tex]
[tex] = x^2 -2xy - 2xy + 4y^2 + 7xy [/tex]
[tex] = x^2 + 3xy + 4y^2 [/tex]